P ( x ) = 5 0 0 x 4 9 9 + 4 9 5 x 4 9 8 + 4 9 0 x 4 9 7 + 4 8 5 x 4 9 6 … − 1 9 9 0 x − 1 9 9 5
Consider the 499th degree polynomial above.
If P ( 2 ) can be written as a + b × c d where a , b , c , d are positive integers and c is not a perfect k th power, find the smallest positive integral value of f satisfying a + b + c + d ≡ f ( m o d 5 0 0 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This is simply an arithmetico-geometric progression , with
First term of A P = a 1 = − 1 9 9 5 , Common difference = d = 5 and 500th term = a n = 5 0 0
First term of G P = b 1 = 1 , Common ratio = r = x = 2 and 500th term = 2 4 9 9
Sum of n terms of such progression is given by
1 − r a 1 b 1 + ( 1 − r ) 2 d b 1 r ( 1 − r n − 1 ) − 1 − r a n b n r
Substituting the values , = 1 − ( 2 ) ( − 1 9 9 5 ) ( 1 ) + ( 1 − 2 ) 2 ( 5 ) ( 1 ) ( 2 ) ( 1 − 2 5 0 0 − 1 ) − 1 − 2 ( 5 0 0 ) ( 2 4 9 9 ) ( 2 )
= − 1 − 1 9 9 5 + 1 ( 5 ) ( 2 ) ( 1 − 2 4 9 9 ) − − 1 ( 5 0 0 ) ( 2 5 0 0 )
= 1 9 9 5 + 1 0 + 5 0 0 ( 2 5 0 0 ) − 5 ( 2 5 0 0 )
= 2 0 0 5 + 4 9 5 ( 2 5 0 0 )
a + b + c + d = 2 0 0 5 + 4 9 5 + 2 + 5 0 0 = 3 0 0 2 = e
3 0 0 2 ≡ 2 ( m o d 5 0 0 )
⇒ f = 2 (smallest value)
Problem Loading...
Note Loading...
Set Loading...
We have P ( 2 ) = S = 5 0 0 ( 2 4 9 9 ) + 4 9 5 ( 2 4 9 8 ) + 4 9 0 ( 2 4 9 7 ) + … − 1 9 9 0 ( 2 1 ) − 1 9 9 5 : E q . 1
Multiplying 2 by Eq.1 in both the Left hand side, and well as Right Hand Side, we obtain:
=> 2 S = 5 0 0 ( 2 5 0 0 ) + 4 9 5 ( 2 4 9 9 ) + 4 9 0 ( 2 4 9 8 ) + … − 1 9 9 0 ( 2 2 ) − 1 9 9 5 ( 2 1 ) : E q . 2
Subtract E q . 2 from E q . 1 to obtain:
=> S = 5 0 0 ( 2 5 0 0 ) − 5 ( 2 4 9 9 ) − 5 ( 2 4 9 8 ) − 5 ( 2 4 9 7 ) − … − 5 ( 2 1 ) + 1 9 9 5
=> S = 5 0 0 ( 2 5 0 0 ) − ( 5 ) ( 2 ) [ 2 4 9 8 + 2 4 9 7 + 2 4 9 6 + … + 2 1 + 1 ] + 1 9 9 5
=> S = 5 0 0 ( 2 5 0 0 ) − ( 5 ) ( 2 ) [ 2 4 9 9 − 1 ] + 1 9 9 5
=> S = 5 0 0 ( 2 5 0 0 ) − 5 ( 2 5 0 0 ) + ( 5 ) ( 2 ) + 1 9 9 5
=> S = 2 0 0 5 + 4 9 5 ( 2 5 0 0 )
=> Therefore we have a = 2 0 0 5 ; b = 4 9 5 ; c = 2 ; d = 5 0 0 ; e = 3 0 0 2 ; and f = 2